Indocyanine Green Retention Test as a Predictor of Postoperative Complications in Patients with Hepatitis B Virus-Related Hepatocellular Carcinoma - Mai RY; Bai T; Luo XL; Wu GB (Dove Medical Press, 2022)
Rong-Yun Mai,1,2 Tao Bai,1 Xiao-Ling Luo,2 Guo-Bin Wu1 1Department of Hepatobiliary & Pancreatic Surgery, Guangxi Medical University Cancer Hospital, Nanning, 530021, People's Republic of China; 2Department of Experimental Research, Guangxi Medical University Cancer Hospital, Nanning, 530021, People's Republic of ChinaCorrespondence: Guo-Bin Wu; Xiao-Ling Luo, Email wuguobin@gxmu.edu.cn; luoxiaoling67@126.comBackground: Accurate preoperative estimation of liver function reserve is the key to the safety of hepatectomy. Recently, indocyanine green retention test at 15 minutes (ICG-R15) has been widely used to estimate hepatic function reserve in different liver diseases. The purpose of this research was to investigate the clinical value of ICG-R15 in predicting postoperative major complications and severe posthepatectomy liver failure (PHLF) in patients with hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) subjected to hepatectomy.Methods: A total of 354 HBV-associated HCC patients who underwent hepatectomy were enrolled. The Child-Pugh, model for end-stage liver disease (MELD), albumin-bilirubin (ALBI) and ICG-R15 for assessing postoperative complications risk were compared using receiver operating characteristic (ROC) curve and decision curve analysis (DCA).Results: Postoperative major complications developed in 32 patients (9.1%) and severe PHLF developed in 57 (16.1%) patients. Multivariate analyses revealed that ICG-R15 were independent factors for predicting postoperative major complications and severe PHLF. ROC curve analyses and DCA plots showed that the predictive abilities of ICG-R15 for postoperative major complications and severe PHLF risk was significantly greater than Child-Pugh, MELD, and ALBI scores. Similar results were obtained by stratifying different background subgroups. Then, patients were divided into three different risk cohorts, emphasizing the significantly discrepancy between the incidence of postoperative major complications and severe PHLF.Conclusion: Compared with Child-Pugh, MELD and ALBI scores, ICG‐R15 revealed significantly advantages in predicting postoperative major complications and severe PHLF in HBV-related HCC patients subjected to liver resection.Keywords: hepatocellular carcinoma, hepatitis B virus, postoperative major complications, posthepatectomy liver failure, indocyanine green retention test